The role of «Smart city» concept in social infrastructure management of single-industry towns - Yessengeldin, B.S.; Mukhamediyeva, G.M.; Akybayeva, G.S.; Zhanseitov, A.T. (BUKETOV BUSINESS REVIEW, 2018)
The article deals with the theoretical foundations of the concept of «smart city». The authors of the article studied the scientific works which devoted to the research and development of technological components of Smart City and their implementation in various areas of the city (transport infrastructure, social infrastructure, e-government services, e-business and others). The article presents international practice to determine the factors that form the content of initiatives to create smart cities. The main attention is paid to the role of standardization, which covers many aspects of the design, organization and functioning of the smart city. The authors describe the national standards in the field of Smart City, which regulate the unified requirements for fundamentally new possibilities of centralized management of urban processes. The article defines the functions and tasks of the social infrastructure of single-industry towns, which should be taken into account in the implementation of the concept of Smart City. Selected areas of activity specified in the concept of Smart City, which are closely related to the development of social infrastructure of single-industry towns of Kazakhstan: medical care; education; social services; public services; movement around the city; emergency. The authors of the article identify the practical benefits received by citizens of single-industry towns from the application of the concept of Smart City in social infrastructure